Travel abroad increases sexual health risk-taking among Swedish youth: a population-based study using a case-crossover strategy - Mats Sundbeck; Anette Agardh; Per-Olof Östergren (Taylor & Francis Group, 2017)
Background: The fact that youth take sexual risks when they are abroad have been shown in previous studies. However, it is not known if they increased their sexual risk-taking when travelling abroad, compared to the stay in their homeland. Objective: To assess whether Swedish youth increased their individual sexual risk behaviour, defined as having a casual sex partner, when travelling abroad and to examine possible factors that may be associated with increased risk-taking abroad. Design: In 2013, a population-based sample of 2189 Swedes, 18-29 years, was assessed by a questionnaire (45% response rate). Sexuality, duration of travel, parents' country of origin, mental health, heavy episodic drinking (HED), use of illicit drugs, and socio-demographic background were assessed. Increased risk of casual sex in relation to time spent abroad vs. time spent in Sweden was analysed by a variant of case-crossover design. Factors that could be associated with increased risk of casual sex in Sweden and abroad, separately, were analysed by logistic regression.